PERAN KANTOR KEMENTERIAN AGAMA KOTA YOGYAKARTA DALAM KEBIJAKAN PENGEMBANGAN PENDIDIKAN ISLAM - Millah, Nur Ita A?ini Qudwatal; Maghfuri, Amin (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2019)
The specialty of one of the things that underlies Yogyakarta is called a student city of course because of the educational climate in the region. With a work area that is relatively not too broad and the quantity of institutions that are not too many the Ministry of Religion is one of the government agencies, especially in the field of Islamic Education. This is certainly able to make it as an advantage and convenience in creating the development of Islamic education in the work area that is superior to other work areas. The research method used in this research is a qualitative descriptive study. Data collection techniques through observation, interviews, and study documentation. The results of this study indicate that in general educational policy in the aspect of developing / fostering Islamic Education in the Ministry of Religion in Yogyakarta is more guided than the RI Ministry of Religion program. However, in its implementation in the city of Yogyakarta, these programs are relatively easier to do, one of which is because the area coverage is not too broad. Institutionally, within the framework of the policy of developing Islamic education guidance in the Ministry of Religion of the City of Yogyakarta dividing management responsibilities to three work units, namely the Islamic Education Section (PAIS), the Madrasah Education Section (PENMAD) and the Diniyah Education Section and Islamic Boarding School (PD PONTREN). The Islamic Education Section (PAIS) has a working area on fostering and managing Islamic education in public schools at all levels, the Madrasah Education Section (PENMAD) in Islamic education houses all levels in Madrasas as well as the Diniyah Education and Islamic Boarding Schools (PD PONTREN) responsible responsible for fostering ongoing Islamic education in Madrasah Diniyah including TPA and Islamic Boarding School, so that each of these sections has a policy of developing Islamic Education in its own work program.